Differential responses in growth, physiological processes and peroxidase activity of young mango (Mangifera indica) and citrus (Citrus sinensis L) plants to water deficit - Ismail, Mohd Razi; Muhammad, Abd Ghani; Iberahim, Ismail (Universiti Putra Malaysia Press, 2004)
mango (Mangifera indica) and citrus (Citrus sinensis L) plants in the greenhouse. Under gradually decreasing soil moisture content, mango and citrus differed in their leaf water potential, stomatal conductance, leaf growth and peroxidase activity. Stomata of both plants responded independently to the changes in leaf water potential as soil drying progressed. The reduction in stomatal conductance in mango was greater than citrus suggesting that citrus was able to control water loss better than mango to the changing condition of water availability in the root zone. Peroxidase activity increased significantly in water stressed citrus plants. There was a 6-10 fold increase in proline content when both species were exposed to water stress. Citrus plants accumulated higher proline levels suggesting that they can tolerate water stress compared to mango. This was also evident by a faster recovery after rewatering in citrus compared to mango plants that involved regeneration of new shoots.